Milestones in the history of neurocritical care - Rainer Kollmar; Michael De Georgia (Neurological Research and Practice, 2023)
Abstract Over the last century, significant milestones have been achieved in managing critical illness and diagnosing and treating neurological diseases. Building upon these milestones, the field of neurocritical care emerged in the 1980 and 1990 s at the convergence of critical care medicine and acute neurological treatment. This comprehensive review presents a historical account of key developments in neurocritical care in both the United States and Europe, with a special emphasis on German contributions. The scope of the review encompasses: the foundations of neurocritical care, including post-operative units in the 1920s and 30s, respiratory support during the poliomyelitis epidemics in the 40 and 50 s, cardiac and hemodynamic care in the 60 and 70 s, and stroke units in the 80 and 90 s; key innovations including cerebral angiography, computed tomography, and intracranial pressure and multi-modal monitoring; and advances in stroke, traumatic brain injury, cardiac arrest, neuromuscular disorders, meningitis and encephalitis. These advances have revolutionized the management of neurological emergencies, emphasizing interdisciplinary teamwork, evidence-based protocols, and personalized approaches to care.